2020
DOI: 10.1186/s12882-020-01751-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in acute kidney injury in noncritically ill patients lately referred to nephrologist in a developing country: a comparison of AKIN and KDIGO criteria

Abstract: Background: In low-middle-income countries (LMICs), data regarding acute kidney injury (AKI) are scarce. AKI patients experience delayed diagnosis. This study aimed to evaluate whether delayed nephrologist consultation (NC) affected outcomes of AKI patients and compare Acute Kidney Injury Network (AKIN) and Kidney Disease: Improving Global Outcomes (KDIGO). Methods: An observational, retrospective study was conducted in a tertiary public hospital in an LMIC. Results: Overall, 103 AKI patients were analysed. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 32 publications
2
17
0
4
Order By: Relevance
“…Balasubramanian et al showed a significant risk reduction of further kidney function deterioration if renal consultations took place within 18 hours of AKI-onset [9,33]. Delayed consultations in our cohort might have been due to missed diagnosis and a lack of consciousness of the significance of timely intervention [34] and could be improved by the AMPEL-CDSS as well.…”
Section: Plos Onementioning
confidence: 64%
“…Balasubramanian et al showed a significant risk reduction of further kidney function deterioration if renal consultations took place within 18 hours of AKI-onset [9,33]. Delayed consultations in our cohort might have been due to missed diagnosis and a lack of consciousness of the significance of timely intervention [34] and could be improved by the AMPEL-CDSS as well.…”
Section: Plos Onementioning
confidence: 64%
“…Fatores socioeconômicos e ambientais, destacando-se a escassez de alimentos, influenciam a evolução da injuria renal aguda das cardiopatias e da síndrome cardiorrenal, conexões habitualmente ignoradas em muitos estudos. 6,7 A pesquisa em questão foi desenvolvida em hospital terciário, principal referência no atendimento de emergência de uma população de aproximadamente 1 milhão de pessoas, em um estado do Brasil de baixo desenvolvimento econômico (22 o lugar entre 27 unidades da federação no quesito Produto Interno Bruto [PIB]). 6,7,11 No presente estudo, no entanto, identificou-se que as características clínicas e demográficas foram semelhantes às de trabalhos encontrados na literatura, constituindo-se de uma população de idosos predominantemente masculina, como mostrado por Spineti et al, 3 com 58% da população estudada deste gênero e média de idade de 63,5 ± 13 anos.…”
Section: Discussionunclassified
“…6,7 A pesquisa em questão foi desenvolvida em hospital terciário, principal referência no atendimento de emergência de uma população de aproximadamente 1 milhão de pessoas, em um estado do Brasil de baixo desenvolvimento econômico (22 o lugar entre 27 unidades da federação no quesito Produto Interno Bruto [PIB]). 6,7,11 No presente estudo, no entanto, identificou-se que as características clínicas e demográficas foram semelhantes às de trabalhos encontrados na literatura, constituindo-se de uma população de idosos predominantemente masculina, como mostrado por Spineti et al, 3 com 58% da população estudada deste gênero e média de idade de 63,5 ± 13 anos. Liangos et al 11 demonstrou predominância de homens, idosos e DM, HAS e DRC as principais comorbidades associadas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Although not available in all low-resource settings, serum creatinine laboratory values are the most commonly used tools to identify AKI. 1,35,[38][39][40][41][42][43][44][45][46][47][48][49][50] A 2015 multinational cross-sectional study showed that the diagnosis of AKI was made with serum creatinine values alone in 63% of participating facilities, followed by serum creatinine along with urine output in 28% of participating facilities in LMICs. 1 A 2018 qualitative study surveying AKI identification and management practices among 160 intensivists based in provincial and regional hospitals in Thailand showed that the KDIGO criteria for AKI were most commonly used (37%), followed by the AKIN (27.7%) and RIFLE (26.1%) criteria, respectively.…”
Section: Questionsmentioning
confidence: 99%